The Relationship between the Effectiveness of In-Service Training of Employees and Occupational Consequences in Aboozar Hospital in Ahvaz, Iran - Shohreh Banidavoodi; Mahin Atabi (Tehran University of Medical Sciences, 2017)
Background and Aim: Due to the unprecedented growth of health management information, it is necessary to train human forces working in hospitals. Therefore, this study was conducted to identify the relationship between in-service training of staff in Aboozar hospital on the one hand and organizational commitment, job satisfaction, and organizational citizenship behavior (OCB) on the other.  Materials and Methods: We conducted this cross-sectional (descriptive-analytic) study on the statistical population of Aboozar hospital in Ahvaz in 2015. One hundred hospital employees were selected. The data collection instruments included a researcher-made questionnaire for the evaluation of in-service training, Smith and Organ's OCB questionnaire, Fishman and Common's questionnaire of job satisfaction, and Balfour and Wechsler's organizational commitment questionnaire. We analyzed the data using descriptive statistics as well as ANOVA.  Results: The results showed that there was a significant relationship between  in-service training of employees and job satisfaction (r=0.53, P<0.001), organizational commitment (r=0.3, P=0.004) and OCB (r=0.36, P< 0.03).  Conclusion: Because of the relationship between the importance of performance and staff members' qualification -- that is achieved following effective training -- in health system, employees' job training average score was at an optimum level; but the nursing staff's mean score of training, job satisfaction, organizational commitment and administrative OCB was lower than that of other staff. Therefore, the necessity to pay attention to the training of staff, especially nurses, becomes more and more evident. Besides, the goals of education will be achieved more easily, that is, employees' performance will be improved.